- PENGUATAN PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS IT MGMP IPA BLORA: - - Sigit Ristanto; Joko Saefan; Nur Khoiri; Affandi Faisal Kurniawan (LPPI UMN AL WASHLIYAH, 2025)
Science teachers of the Blora Regency MGMP experienced obstacles in creating IT-based learning media. The purpose of this PKM activity is to provide assistance to science teachers in creating IT-based learning media for the science learning process in junior high schools as part of teacher professional development. The methods used in this activity are socialization, workshops, and mentoring. Socialization is carried out to agree on the implementation of community service. The workshops that will be implemented include: Designing IT-based interactive learning media with a deep learning approach, Creating AI-based interactive learning media, Utilizing PheT-based interactive learning media, and implementing interactive learning media. In addition to the workshop, this community service activity also provides assistance in creating IT-based media starting from the stage of analyzing media needs, creating AI-based media, and PheT. This activity was carried out for 32 hours of lessons and monitoring the use of learning media by Blora Regency MGMP Science teachers. The results of the community service showed that all participants were able to utilize AI and PhET Simulation in preparing learning media. This was shown in the learning media that had been prepared by participants after completing the community service.